Hubungan Bimbingan Belajar Orang Tua dan Konsep Diri dengan Hasil Belajar Matematika - IKJ Wirawan; I Made Suarjana; N.T. Renda (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to determine: (1) the relationship between parents learning guidance with the results of learning mathematics, (2) the relationship between self-concept with the results of learning mathematics, (3) relationship between parents learning guidance and self concept with the result of learning mathematics of third grade semester II at SD Gugus XII Buleleng District, in the academic year 2017/2018. The type of research is used a correlation research. The population of this study amount to 169 people with a total sample of 114 people took by the technique of Proportional Random Sampling. The data of parents course and self-concept is collected through filling the questionnaire, whileÂ  result of data learning mathematics obtained by document recorder (document analyze). The data were analyzed by descriptive statistic technique and regression analysis. The results of data analysis show: (1) the relationship between parents learning guidance with mathematics learning outcome of = 0,367 and the coefficient of determination of 13.5%, meaning there is a significant relationship between parents course with the results of learning mathematics. (2) the relationship between self-concept with the result of learning mathematics of = 0,450 and coefficient of determination equal to = 20,3%, meaning there is a significant correlation between self concept and the result of learning mathematics. (3) the relationship between parents learning guidance and self concept with the result of learning mathematics equal to = 0,461 and coefficient of determination equal to = 21,3%, meaning there is significant correlation between parents course and self concept with the result of learning mathematics.